Second-Degree Moral Hazard in a Real-World Credence Goods Market - Loukas Balafoutas; Rudolf Kerschbamer; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2013)
Empirical literature on moral hazard focuses exclusively on the direct impact of asymmetric information on market outcomes, thus ignoring possible repercussions. We present a field experiment in which we consider a phenomenon that we call second-degree moral hazard - the tendency of the supply side in a market to react to anticipated moral hazard on the demand side by increasing the extent or the price of the service. In the market for taxi rides, our moral hazard manipulation consists of some passengers explicitly stating that their expenses will be reimbursed by their employer. This has an economically important and statistically significant positive effect on the likelihood of overcharging, with passengers in that treatment being about 13% more likely to pay higher-than-justified prices for a given ride. This indicates that second-degree moral hazard may have a substantial impact on service provision in a credence goods market.
Keywords: C93; D82; 330; natural field experiment; credence goods; asymmetric information; moral hazard; overcharging; overtreatment; taxi